Unearthing the essence of nature and the perception of the natural landscape among the amaXhosa in the Eastern Cape : an exploratory study - Mogano, Lydia Lehlogonolo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
The recognition of the close link between the lifestyles of 'indigenous' and 'local' people and biodiversity is widely acknowledged as crucial, not only for the survival of biological diversity but also for the protection of cultural diversity. Most discussions centre on the argument that cultural diversity can, through a wide variety of uses and practices, sustain and conserve biodiversity, particularly in many developing countries. However, local people's relationship with natural landscapes and the extent to which they value biodiversity has not been fully explored and is in most cases misunderstood, which in fact undermines the bio-cultural diversity link. This misunderstanding exists primarily because the majority of environmental or ecological research conducted so far has been oriented towards economic valuation, in quantifying the estimated value of plants and fauna utilised by local people. As a result, biodiversity is primarily treated as a commodity, with wild harvested plant products being classified as either having subsistence, or commercial and medicinal value. This approach is narrow and conceals the critical, profound noneconomic values of biodiversity among local communities in everyday life. Literature indicates that biodiversity and natural landscapes also include less tangible values such as spiritual, cultural, psychological and social values (e.g., sense of place, place attachment, and psychologically restorative effects) which are crucial to human well-being. This suggests that human-nature interaction is complex, and that the meanings and values that people ascribe to natural landscapes cannot be solely reduced to economic values. Nevertheless, to date, studies investigating these less tangible values have received little attention in South Africa. As a result, we have very little understanding of what local and indigenous communities value or appreciate with regard to natural landscapes, beyond their general economic significance. This study seeks to address this particular limitation by exploring non-economic values of natural landscapes and their significances to local people while illuminating the complexities inherent in human-nature interactions. I argue that the purely economic valuation of natural resources is simplistic and biased, and therefore does not represent the complete meaning and significance that natural resources may hold for local communities and households. Therefore, this study takes an innovative psychological approach to explore in detail the everyday lived experiences of the amaXhosa in the Eastern Cape, South Africa. It seeks to investigate the cultural, spiritual, and psychological values that ordinary people attach to natural landscapes in the peri-urban and urban communities of Ndlambe Village l and Grahamstown respectively. This research also aims to study the general perceptions of and meanings ascribed to the natural landscape (referred to by the amaXhosa as ihlathi lesiXhosa). In addition, it carefully integrates the Phenomenological and Transactional approaches to investigate how the amaXhosa engage, interact, and find meaning within the natural landscape. Furthermore, the study explores the impact of such landscape experiences on local people's spiritual and psychological well-being, demonstrating it link to bio-cultural diversity and conservation. The major findings in this study reflect that ihlathi lesiXhosa provides a place for peace and tranquillity to enhance psychological restoration. Moreover, ihlathi contributes towards redefining and strengthening personal and cultural identity
Keywords: Xhosa (African people) -- South Africa -- Eastern Cape; Conservation of natural resources -- South Africa -- Eastern Cape; Biodiversity conservation -- South Africa -- Eastern Cape; Cultural pluralism -- South Africa -- Eastern Cape; Human-plant relationships -- South Africa -- Eastern Cape; Human ecology -- South Africa -- Eastern Cape